LANDASAN TEOLOGIS PENGAWASANDI LEMBAGA PENDIDIKAN ISLAM PERSPEKTIF AL QUR’AN (Kajian Terhadap Ayat Kursi Tentang Pengawasan) - *, Suyanto (QUALITY, 2013)
There are so many verses of the Qur’an which describes the supervision. Although the verses does not specifically talk aboutsurveillance in Islamic educational institutions, but the spiritwhich is implicit role in the verses gives a lesson to us to conductsurveillance. One is Ayat Kursi who is the prince of verses of theQur’an. This study uses a qualitative approach method by libraryresearch. As for the issues discussed, the writer used descriptiveanalytical discussion. The study begins with the data and thendoes the analysis to obtain a discussion that can be justifiedscientifically. Results from this study is that this verse can be usedas a theological foundation in Islamic educational institutionssupervision because Ayat Kursi outlining the divine nature of God.If we believe wholeheartedly the existence and the nature of God in the Ayat Kursi, the supervision in Islamic educational institutions will go well.